Pengaruh Pola Tinggal terhadap Kemampuan Menghafal Al Qur’an: Studi Komparatif Antara Santri Mukim dan Non Mukim - Shofiatul Fuadah; Siti Rofiah; Suwardi Suwardi; Wahyu Hidayat; Dina Indriana (Universitas Palangka Raya, 2024)
Islamic boarding schools are boarding educational institutions. However, at the Shohibul Muslimin Islamic boarding school, some students are allowed not to live in the Islamic boarding school area. So, these environmental differences have an influence on the development of students' learning outcomes and memorization of the Koran. This research aims to determine the differences in the results of memorizing the Koran by resident and non-resident students at the Shohibul Muslimin Islamic boarding school in Serang. This research uses a comparative study. The subjects of this research were class 11 students consisting of 34 students, but the samples taken were only 5 residential students and 5 non-resident students. This research uses rote test data collection techniques with expert examiners. The data was analyzed using prerequisite analysis tests including homogeneity and normality tests, independent sample T-test. So, based on the results of this research, it indicates that there is a significant difference in the results of memorizing the Al-Quran for mukim and non-resident Islamic boarding school students at the Shohibul Muslimin Islamic boarding school. So it can be seen from the average result of the Al-Quran memorization test for mukim students, it is 8.50 and the average result of the Al-Quran memorization test for non-resident students is 7.40. And the Independent Sample T-test results obtained a sig value of 0.025 < 0.05, which means that the Ho value is rejected. So it can be concluded that there is a significant difference in the ability of Al-Quran memorization test results between residential students and non-resident students.